Una ojeada curiosa al Registro General del Sello (documentos sobre cristianos y musulmanes durante el reinado de Isabel la Católica) - Ávila Seoane, Nicolás (Documenta & Instrumenta - Documenta et Instrumenta, 2007)
Selection of unpublished documents of the Registro General del Sello of the end of the 15th century about the relationship between Christians and Moslems, from the main institutions point of view (war against the infidels, conquest expeditions, arms, piracy) and also from the individuals’ perspective (robberies, neighbour arguments, protests applied to the kings, rescue of slaves), all with the constant feature of the curious aspect’s subject. In addition to the complete transcription of the texts is incorporated a brief historical study of each one.